Prognostic and clinicopathological impact of systemic inflammation response index (SIRI) on patients with esophageal cancer: a meta-analysis - Zhong Wu; Zongxin Zhang; Chao Gu (Systematic Reviews)
Abstract Background Although the systemic inflammation response index (SIRI) is often associated with prognostic significance in esophageal cancer (EC) patients, the results continue to be conflicting. We focused on identifying SIRI’s precise role in forecasting EC prognosis through performing this meta-analysis. Methods This work searched PubMed, Web of Science, Embase, Cochrane Library, and CNKI till November 16, 2024, and determined pooled hazard ratios (HRs) and 95% confidence intervals (CIs) for evaluating EC prognosis forecasting efficiency of SIRI. The inclusion criteria: (1) pathologic confirmation of EC; (2) those reporting associations of SIRI with EC survival outcomes; (3) those reporting HRs and 95% CIs; (4) those with an available cut-off value of SIRI; and (5) no restriction in language. The exclusion criteria: (1) case reports, reviews, meeting abstracts, comments and letters; (2) those enrolling duplicate cases; and (3) animal studies. Results We enrolled six studies comprising 2176 cases into the present work. Based on our combined findings, elevated SIRI showed significant relation to dismal overall survival (OS) (HR = 1.43, 95%CI = 1.20–1.71, p < 0.001; I2 = 48.8%, p = 0.098) and shortened progression-free survival (PFS) (HR = 2.00, 95%CI = 1.35–2.98, p = 0.001; I2 = 0, p = 0.409) in EC. Moreover, high SIRI exhibited obvious relation to male gender (OR = 1.86, 95%CI = 1.07–3.22, p = 0.027; I2 = 69.4%, p = 0.020), TNM stage of III-IV (OR = 1.52, 95%CI = 1.18–1.94, p = 0.001; I2 = 24.3%, p = 0.265), T3-T4 stage (OR = 1.73, 95%CI = 1.12–2.69, p = 0.014; I2 = 61.0%, p = 0.053), and lymph node metastasis (OR = 1.29, 95%CI = 1.02–1.64, p = 0.036; I2 = 42.7%, p = 0.155). However, SIRI was not markedly related to age, tumor location, tumor differentiation, or smoking history. Conclusion In summary, high SIRI is significantly related to dismal OS and shortened PFS of EC cases, together with advanced tumor stage, T3-T4 stage, and lymph node metastasis of EC. Due to some limitations, large prospective studies that utilize standardized threshold SIRI should be conducted to validate our results in the future.